Kompetencje akademickie studentów neofilologii. Postrzeganie problematyzacji w artykule naukowym - Karpińska-Szaj, Katarzyna; Wojciechowska, Bernadeta (Neofilolog, 2024)
The aim of the article is to summarize current trends in research on advanced skills in reading and writing academic texts and to analyze the ways in which a research paper may be explored by students of modern language studies at master’s degree level. The cited examples of strategies for reconstructing the logic of a research paper refer to the perception and expression of knowledge from a specialized field in verbal interactions, after completing a task which combines reading a selected research paper and using its content in their own text. The main aspect of the analysis is problematization, construed as the principal (structural and logical) axis of an academic text.